Socialization of Historical Values and Heritage in Medan Through Heritage Goes to School Activities - Kiki Maulana Affandi; Junaidi Junaidi; Rahmatika Luthfiana Sholikhah (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
Community service is one of the three pillars of higher education. The community service activity entitled Heritage Goes to School is a way of introducing heritage and historical values to high school students. This activity includes socialization and efforts to preserve heritage in the city of Medan so that historical and cultural heritage is not lost in the memory of the younger generation. The Heritage Goes to School activity collaborates with the partner Beranda Warisan Sumatera (BWS). BWS is a non-profit organization that focuses on raising awareness about the importance of preserving cultural heritage. The collaboration with the BWS community aims to disseminate historical values and heritage to the community, especially the younger generation, namely high school students. The location for Heritage Goes to School was Madrasah Aliyah Al-Azhar Asy-Syarif North Sumatra High School. Heritage Goes to School was carried out by presenting the history of Medan City and its heritage, followed by heritage games as an effort to introduce historical and heritage values to high school students in a fun way. This was done as a step to socialize historical values and heritage and attract the interest of the younger generation in heritage preservation. The outputs of this activity were the publication of a socialization video on YouTube, news publications in the national media, and article publications in national journals.